Sexual assault survivors’ perspectives on enablers of and barriers to clinical follow-up at three facilities in the Eden District - Holton, Gail Allison (Stellenbosch : Stellenbosch University, 2016)
Thesis (MCur)--Stellenbosch University, 2016.